1978
DOI: 10.1002/ijc.2910210612
|View full text |Cite
|
Sign up to set email alerts
|

The effect in vivo of chemotherapeutic drug—antibody conjugates in two murine experimental tumor systems

Abstract: Conjugates of daunomycin covalently coupled, either directly or through a dextran bridge, t o antibodies reacting selectively with tumor cells, were tested for their capacity t o suppress tumor development in mice. The drug-antibody conjugates, or mixtures of drug and antibody, were compared either to the free drug or t o the drug coupled to normal immunoglobulin for their effect on two tumor systems. In the f i r s t case, a plasmacytoma (PCS), both the drug and the tumor cells were administered by the same r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Conjugates with doxorubicin were prepared successfully in our laboratory (9,12,14), as well as by others (15,16). We report here the preparation of drug-mAb conjugates of high drug-to-mAb molar ratio, which specifically bind to the EGF receptor and exert cytotoxic effects on KB tumors in nude mice.…”
Section: Resultsmentioning
confidence: 94%
“…Conjugates with doxorubicin were prepared successfully in our laboratory (9,12,14), as well as by others (15,16). We report here the preparation of drug-mAb conjugates of high drug-to-mAb molar ratio, which specifically bind to the EGF receptor and exert cytotoxic effects on KB tumors in nude mice.…”
Section: Resultsmentioning
confidence: 94%
“…Daunomycin hydrochloride (Farmitalia, Milano, Italy) was bound to horse and monoclonal antibodies to rat AFP or to normal horse immunoglobulin via a dextran bridge as described (17).…”
Section: Methodsmentioning
confidence: 99%
“…Assessments of the cytotoxic effectiveness of the antibody-methotrexate conjugates in vitro, using measurements of both 5"Cr release from pre-loaded cells (Figure 4) and cell population parameters (Figure 2) (Kulkarni et al, 1981;Lee & Hwang, 1979;Tai et al, 1979) and in some cases an enhanced effect has been observed over the conjugate (Hurwitz et al, 1978).…”
Section: Discussionmentioning
confidence: 99%